Effects of an interdisciplinary programme on psychoemotional factors in informal caregivers of people with Alzheimer’s disease - Muñoz-Bermejo, Laura; Urbano-Mairena, Javier; Calle-Guisado, Violeta; Mendoza-Holgado, Cristina; Jerez-Barroso, María del Rocío; Suárez-Lantarón, Belén; López-Gil, José Francisco; Barrios-Fernández, Sabina (Frontiers in Psychology, 2025)
Alzheimer’s disease (AD) causes a progressive deterioration in the person’s memory and cognitive function, leading to a greater degree of dependency as the disease progresses. This causes a progressive increase in caregiver overload, leading to physical, psychological, and social impairments. This study aimed to evaluate the effects of a nine-month interdisciplinary intervention covering three areas (cognitive-behaviour, psycho-emotional, and physical activity) on various psycho-emotional variables in informal caregivers of people with AD. A trial was conducted in which 59 informal caregivers of people with AD were administered various instruments to assess psychoemotional aspects (EuroQol-5 Dimensions-3 Levels, Zarit Burden Inventory test, Satisfaction with Life Scale, General Happiness Questionnaire, Occupational Balance Questionnaire, Rosenberg Self-esteem Scale, Duke-UNC-11 Functional Social Support Questionnaire, and the Family Apgar Scale). Significant between-group improvements were obtained in occupational balance at 3 (p = 0.002), 6 (p = 0.013) and 9 months (p = 0.022) of intervention, in perceived social support at 3 months (p = 0.043) and satisfaction with life at 6 months (p = 0.020). No significant between-group differences were found in the remaining variables, although there were positive trends in intra-group scores for caregiver overload, quality of life, life satisfaction and family functioning. Thus, an interdisciplinary programme could have a positive influence on the variables assessed in informal caregivers of AD.